Sustainable development of human settlements : achievements and challenges in housing and urban policy in Latin America and the Caribbean - Mac Donald, Joan...[et al] (UN SantiagoCL, 1998)
Examines aspects such as urban management and equity; managing urban land; the provision of housing and housing technology; environmental management and infrastructure; and sustainable development of human settlements.